Randomised trials of STD treatment for HIV prevention: report of an international workshop. HIV/STD Trials Workshop Group. Issue 6 (December 1997) - Hayes, R; Wawer, M; Gray, R; Whitworth, J; Grosskurth, H; Mabey, D
Abstract : Three community trials of the impact of STD treatment interventions on HIV incidence in rural populations have been completed or are in progress in Uganda and Tanzania. Investigators from these trials met for a joint technical workshop in Baltimore in May 1996. This report summarises the consensus of the workshop, with the aim of providing useful input to research on HIV intervention strategies. Issues discussed include: (i) the role of community randomised trials; (ii) strategies for STD management; (iii) epidemiological and statistical issues in the design and analysis of community randomised trials; (iv) diagnostic methods for STDs in population surveys; (v) treatment regimens for STDs in rural Africa; and (vi) ethical issues in community trials.